FOOD TRADITIONS AND UNUSUAL DISHES (Ustozlar uchun, 2026)
This article examines the relationship between food traditions and unusual dishes from a cultural, historical, and scientific perspective. It explores how traditional foods reflect the identity, values, and social practices of different societies, while also highlighting the role of environment and resource availability in shaping dietary habits.In addition, the study analyzes various types of unusual dishes, including insect-based foods, fermented products, and unconventional animal ingredients, emphasizing their nutritional value and environmental sustainability. The article further discusses the factors that contribute to the development of such foods, including historical challenges, cultural perceptions, and adaptation to local conditions.